Recruiting, Organizing, Planning, and Conducting a 3-Week, Short-Term Study Abroad Program for Undergraduate Students: Guidelines and Suggestions for First-Time Faculty Leaders - Medora, Nilufer; Roy, Roudi Nazarinia (International Journal of Humanities and Social Science Research, 2017)
The article provides an overview on the importance of international education, and the significance of short-term study abroad programs. It also provides specific step-by-step guidelines and recommendations to help first-time faculty members who are interested in conducting a short-term study abroad program in the field of child development and family studies. Explanations are given on conducting orientation sessions before departure, suggestions for fund raising activities, balancing the academic content with recreational and adventure excursions, making arrangements for guest speakers in the host county, arranging for visits to social service agencies, and lastly incorporating service learning activates in the program. Questions such as, “What are some of the of the typical challenges that a faculty leader is likely to encounter in the host country”? are addressed. A summary of the qualitative analyses that was obtained from the students, about their reactions to the program, and the impact that it had on them, after they returned from the 3-week program is explored.